2009
DOI: 10.7150/ijms.6.241
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted closure in the treatment of early hip joint infections

Abstract: The aim of the present study was to evaluate the efficacy of the vacuum-assisted closure (V.A.C.) system in the treatment of early hip joint infections. 28 patients (11 m / 17 f; mean age 71 y. [43-84]) with early hip joint infections have been treated by means of the V.A.C.-therapy. At least one surgical revision [1-7] has been unsuccessfully performed for infection treatment prior to V.A.C. - application. Pathogen organisms could have been isolated in 22/28 wounds. During revision, cup inlay and prosthesis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 12 publications
2
47
0
2
Order By: Relevance
“…A total of 11 studies reporting on 292 cases could be identified ( Figure 1) [2][3][6][7][8][9][10][11][12][13][14] . Two studies were published before and nine after 2000.…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 studies reporting on 292 cases could be identified ( Figure 1) [2][3][6][7][8][9][10][11][12][13][14] . Two studies were published before and nine after 2000.…”
Section: Researchmentioning
confidence: 99%
“…Six studies performed debridement, lavage and change of modular prosthesis components (polyethylene (PE) liner, femoral stem head) [2,3,6,7,9,14] , whereas in one of these studies the PE liner was not changed in all patients [9] . One study combined this procedure along with the use of the vacuum-assisted closure therapy [11] . Two studies reported on partial prosthesis retention [8,13] .…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that the most effective method of prevention and treatment of infected wound complications is topical application of negative pressure -TNP [23][24][25][26][27]. Thus in the study by Condé-Green A [28].…”
Section: Introductionmentioning
confidence: 99%